2003
DOI: 10.1172/jci19270
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of TGF-β1/Smad3 signaling protects against renal tubulointerstitial fibrosis induced by unilateral ureteral obstruction

Abstract: MethodsUUO. Smad3-null (Smad3 ex8/ex8 ) mice were generated as described (13) and were used at 6-8 weeks of age and 20-30 g in body weight. In mice sedated by general anes-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
555
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 523 publications
(595 citation statements)
references
References 48 publications
(25 reference statements)
36
555
1
3
Order By: Relevance
“…For example, TGF-β1 mRNA auto-induction is thought to have a beneficial role in cardiac wound healing after ischemic injury [44] , whilst auto-induction of TGF-β1 at the site of injury in the proximal tubule may result in a positive feedback, where sustained cytokine production may accelerate EMT and increase the generation of myofibroblasts thus promoting and exacerbating fibrosis. A correlation between Smads and AP-1 has also been suggested following elegant studies performed in a mouse model of unilateral ureteric obstruction and in fibroblasts obtained from Smad2 and Smad3 knockout animals [45][46]. These studies confirmed not only a correlation between Smad signalling and TGF-β1 auto-induction, but further demonstrated that the relationship depended on the presence and activation of Smad3.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…For example, TGF-β1 mRNA auto-induction is thought to have a beneficial role in cardiac wound healing after ischemic injury [44] , whilst auto-induction of TGF-β1 at the site of injury in the proximal tubule may result in a positive feedback, where sustained cytokine production may accelerate EMT and increase the generation of myofibroblasts thus promoting and exacerbating fibrosis. A correlation between Smads and AP-1 has also been suggested following elegant studies performed in a mouse model of unilateral ureteric obstruction and in fibroblasts obtained from Smad2 and Smad3 knockout animals [45][46]. These studies confirmed not only a correlation between Smad signalling and TGF-β1 auto-induction, but further demonstrated that the relationship depended on the presence and activation of Smad3.…”
mentioning
confidence: 64%
“…The majority of TGFs regulated in EMT rely on Smad3-dependent transcriptional regulation [45]. Recent studies in renal proximal tubule cells demonstrated angiotensin II-induced tubular EMT was Smad3-dependent [48], whilst (β)1-integrin gene expression, a potential 8 therapeutic target of renal fibrosis is also up-regulated in both unilateral obstruction and in chronic tubulointerstitial fibrosis via a Smad3-dependent mechanism [49].…”
mentioning
confidence: 99%
“…Currently, TGF-␤1 is regarded as the predominant profibrotic stimulus in the kidney and many other tissues (3,17,22). Consistent with this hypothesis, deletion of the downstream effector Smad3 protects against fibrotic disease in the kidney after obstruction (15). TGF-␤1 induces cell hypertrophy in the early phase of fibrotic disease and may promote epithelial cell-to-mesenchyme transition and apoptosis in later stages of fibrotic diseases (9).…”
Section: Discussionmentioning
confidence: 85%
“…Our data indicate that KCP can suppress the TGF-␤ response in renal epithelial cells and help maintain the epithelial phenotype. In animal models of renal disease, TGF-␤ is a profibrotic cytokine that is thought to mediate the transition of epithelial cells to mesenchyme (15,23). Previously, we showed that KCP null mice were hypersensitive to developing renal fibrosis by either the ATN model or the UUO model (11).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in different cell types have already aimed at distinguishing between the specific roles of Smad2 and Smad3, which share biochemical properties, in TGFβ signaling. The majority of these data were obtained from the assessment of transcriptional responses in Smad2 and Smad3 knockout cells, including fibroblasts, hepatocytes, as well as epithelial cells from lens and renal tubules (19)(20)(21)(22)(23)(24). Both of these latter types of epithelial cell also undergo EMT in response to TGFβ, which has been proposed to contribute to fibrosis in the kidney or in the lens after injury.…”
Section: Discussionmentioning
confidence: 99%